2015
DOI: 10.1038/nn.3932
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic basis of opiate suppression of Bdnf gene expression in the ventral tegmental area

Abstract: Brain-derived neurotrophic factor (BDNF) plays a crucial role in modulating neural and behavioral plasticity to drugs of abuse. Here, we demonstrate a persistent down-regulation of exon-specific Bdnf expression in the ventral tegmental area (VTA) in response to chronic opiate exposure, which is mediated by specific epigenetic modifications at the corresponding Bdnf gene promoters. Exposure to chronic morphine increases stalling of RNA polymerase II at these Bdnf promoters in VTA and alters permissive and repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 68 publications
5
65
0
Order By: Relevance
“…Furthermore, morphine seems to suppress the binding of phospho-CREB (cAMP response element-binding protein) and NURR1 (nuclear receptor related-1) to Bdnf promoters in the VTA, resulting in decreased expression of BDNF. In line with this, overexpression of NURR1 in the VTA was shown to decrease morphine-induced place preference, whereas a local knockout of Bdnf could abolish this effect (Koo et al, 2015). …”
Section: Gdnf and Bdnf In Drug Seeking Behavior In Laboratory Animalsmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, morphine seems to suppress the binding of phospho-CREB (cAMP response element-binding protein) and NURR1 (nuclear receptor related-1) to Bdnf promoters in the VTA, resulting in decreased expression of BDNF. In line with this, overexpression of NURR1 in the VTA was shown to decrease morphine-induced place preference, whereas a local knockout of Bdnf could abolish this effect (Koo et al, 2015). …”
Section: Gdnf and Bdnf In Drug Seeking Behavior In Laboratory Animalsmentioning
confidence: 76%
“…Quantitative chromatin immunoprecipitation with antibodies recognizing differentially phosphorylated forms of RNA polymerase II together with a comprehensive analysis of epigenetic regulation of Bdnf gene suggested that exposure to chronic morphine can increase the stalling of RNA polymerase II at Bdnf promoters in the rat VTA (Koo et al, 2015). Furthermore, morphine seems to suppress the binding of phospho-CREB (cAMP response element-binding protein) and NURR1 (nuclear receptor related-1) to Bdnf promoters in the VTA, resulting in decreased expression of BDNF.…”
Section: Gdnf and Bdnf In Drug Seeking Behavior In Laboratory Animalsmentioning
confidence: 99%
“…However, less information is available at the supraspinal level, especially in the mesolimbic reward circuitry. As previously mentioned, BDNF signaling within the mesolimbic reward system has been implicated in several neuropsychological disorders (15, 25, 28, 3133, 55, 58). Here, we found that 1) CCI-induced BDNF protein expression and release in the NAc depended on VTA DA neuron activity; 2) the inhibition of VTA DA neuron firing reversed the established thermal hyperalgesia in CCI mice, which was restored by microinjecting exogenous BDNF into the NAc; 3) the blockade of BDNF signaling in the NAc and inhibition of synthesis in the VTA produced analgesia effects, which were reversed by injecting BDNF directly into the NAc; and 4) selective knockdown of BDNF expression in NAc-projecting VTA neurons reversed CCI-induced thermal hyperalgesia.…”
Section: Discussionmentioning
confidence: 89%
“…This form of neuronal hyperexcitability is a cardinal feature of withdrawal 14,22 , and we demonstrate here that this central tenet of withdrawal occurs directly in the spinal cord of morphine-treated animals. Because opiate withdrawal engages both spinal and supraspinal mechanisms, including the periaqueductal gray 14 , locus coeruleus 23 , ventral tegmental area [24][25][26] and nucleus accumbens 27 , descending inputs from these supraspinal regions may influence spinal facilitation in the intact system. However, our isolated spinal cord preparation suggests that intrinsic spinal mechanisms are sufficient for synaptic facilitation during withdrawal, and as further evidence for a spinal locus of opiate action, we show that spinal manipulations targeting Panx1 channels or ATP levels effectively block or recapitulate the behavioral and cellular corollaries of withdrawal.…”
mentioning
confidence: 99%